Objective Data Reveals Gender Preferences for Patients' Primary Care Physician - Madelinn Fink; Kendall Klein; Kia Sayers; John Valentino; Claudia Leonardi; Amy Bronstone; Pamela M. Wiseman; Vinod Dasa (SAGE Publishing, 2020)
Background and Objectives: Most studies based on self-reported data indicate that female patients more often than males have a same-gender preference for their primary care physician (PCP). Because self-reported preferences may not reflect true preferences, we analyzed objective data to investigate patients' preferences for PCP gender. Methods: Analyses were performed on 2192 new patients seen within a university-based healthcare system by 13 PCPs (2 male, 11 female) during 2017. New patients were asked about their PCP gender preference when assigned a PCP. We compared the expected prevalence (proportion of males/females in overall patient population) and observed prevalence (gender distribution of patients for each PCP) by PCP gender. A mixed model with PCP as a random effect examined the odds of male and female patients being assigned a same-gender physician. Results: The expected prevalence of new patients was 65% female and 35% male. The observed prevalence (95% confidence interval [CI]) of male patients among male and female PCPs was, respectively, 59.7% (49.0%-69.5%) and 28.0% (24.0%-32.4%), with neither CI containing the expected prevalence of male patients (35%). Similarly, the observed prevalence of female patients among male and female PCPs was, respectively, 40.3% (95% CI 30.5%-51.0%) and 72.0% (95% CI 67.6%-76.0%), with neither CI containing the expected prevalence of female patients (65%). Conclusions: Both male and female patients often preferred to see a same-gender PCP with this preference more pronounced in males. Future research should seek to clarify the relationships between patients' gender preferences, patient-physician gender concordance/discordance, patient satisfaction, and health outcomes.